Gender Approach in Professional Orientation of School Students - Maltsev, A; Kasyanova, T; Zubova, L (KnE Life Sciences, 2018)
The Constitution of Russia states that women have the same right to education and professional employment and have the right to equal pay for equal work. However, similarly to most countries, gender asymmetry is observed in Russian labor market. In recent years, a growing number of studies have focused on the topic of gender socialization and its connection to professional self-determination. Our article is devoted to the gender-related aspects of school students’ career choice. We rely on the most recognized methodology in Russia developed by A.G. Shmelev’s group: computer-assisted test battery “Proforientator”. Our research has shown statistically significant differences in future career preferences of male and female students aged between 14 and 18 in all spheres, with the exception of “Communication”. Young men of early adolescence showed great interest in such professional spheres as “Technology”, “Science”, “Business”, “Sign”, and “Risk” while high school girls showed a strong inclination to “Art” and “Nature”. Thus, this distribution of preferences can be considered as a gender-dependent. Our study has also identified masculine characteristics in females and feminine characteristics in males in the formation of their professional interests. We believe that it is important to take into account the process of gender socialization when working to support the professional self-determination of young people. The revealed regularities require further research. Keywords: gender, gender socialization, professional self-determination, interests. professional spheres, professional orientation.